2009
DOI: 10.3111/13696990903123813
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guidelines for sensitivity analysis: cost-effectiveness analyses of dual oral antiplatelet therapy

Abstract: Sensitivity analyses in the cost-effectiveness studies of dual oral antiplatelet therapy were not fully adherent with HTA guidelines. In particular, long-term costs and benefits were not always included in the sensitivity estimates, the impact of differential effects on death and myocardial infarction was not explored, and justification for the alternative parameter values tested was not always provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…[8][9][10] The frequency of retinal breaks in our patients who were taking AC (46%) was significantly lower than the frequency in our patients not taking AC (72%). However, this is still markedly higher than the 2-4% frequency in patients without VH.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…[8][9][10] The frequency of retinal breaks in our patients who were taking AC (46%) was significantly lower than the frequency in our patients not taking AC (72%). However, this is still markedly higher than the 2-4% frequency in patients without VH.…”
Section: Discussionmentioning
confidence: 46%
“…Non-steroidal anti-inflammatory drugs (NSAIDs) also have antiplatelet properties, and their use has increased in the treatment of arthritis. [8][9][10][11][12][13][14][15][16][17][18][19] In this study, we examine the relationship between systemic anticoagulant and antiplatelet usage and the prevalence of retinal breaks and detachment in patients with VH in the setting of an acute PVD.…”
Section: Introductionmentioning
confidence: 99%
“…These results were consistent with the existing literature. Mauskopf and colleagues [11] published a review of the cost-effectiveness of clopidogrel. Part of this review covered eight studies based on the Clopidogrel in Unstable Angina to Prevent Recurrent Events trial [12], including the York-clopidogrel model.…”
Section: Discussionmentioning
confidence: 98%
“…Various clinical studies to compare the effectiveness of antiplatelet administration as a stroke prevention therapy have been carried out. Several studies have shown that single aspirin is more effective than clopidogrel [10,11]. Several trials have tested the efficacy and safety of clopidogrel and aspirin versus aspirin in preventing recurrent stroke in ischemic stroke [12][13][14].…”
Section: Introductionmentioning
confidence: 99%